Implanted β-Tricalcium Phosphate Blocks Can Function as a Placeholder in Recurrent Giant Cell Tumor of Bone. (17th January 2020) - Sakamoto, Akio; Okamoto, Takeshi; Matsuda, Shuichi
Abstract : The giant cell tumor of bone (GCTB) is a locally aggressive tumor. Reconstruction methods using β -tricalcium phosphate ( β -TCP) blocks with strong compression resistance in and around the knee joint for GCTB have been reported. Among six cases of GCTB treated using this method, two recurrent cases revealed osteolysis, predominantly within the β -TCP block based on plain radiographs or computed tomography, while remodeled host bones were preserved. Implanted β -TCP blocks can function as a placeholder to preserve host bone in recurrent cases, leading to a higher probability of joint preservation.